Radiographic Assessment of the Prevalence of Pulp Stones in Hazaribag Population – Original Research - Songa Sushmita Naidu, Deepyanti Dubey, Gurinder Kaur, Karpagavalli Shanmugasundaram, Deepak Kurup, Rakhi Singh (Drugs and Cell Therapies in Hematology, 2021)
Objective: The aim of this study was to determine the prevalence of pulp stones (PS) in a Hazaribag dental patient population with respect to sexes and dental localization in relation between sex and this anomaly. Materials methods: A retrospective study was performed using bitewing radiographs of 814 patients ranging in age from 15 to 65. All data (age, sex, and location) was obtained from the files. These patients were analyzed for pulp stones. Descriptive characteristics of sexes, jaws, and dental localization were recorded. The Pearson chi- squared test was used. Results: Of the patients, 462 (56.8%) were female and 352 (43.2%) were male. Sixty (12%) had one or more teeth that contained pulp stones. Pulp stones were identified in 518 (63.6%) of the subjects and in 2391 (27.8%) of the teeth examined. Pulp stone occurrence was significantly more common in the females than in males. With the increasing of age, the prevalence of pulp stones increased. Molars had statistically more pulp stones than premolars. Pulp stones were significantly more common in the maxilla compared with mandible. Conclusion: Prevalence of pulp stones in Hazaribag population was 27.8% but further larger-scale studies are required to assess its prevalence in the general population to compare it with other ethnic groups.